Insights Into Bone Marrow Niche Stability: An Adhesion and Metabolism Route - Ashok, Driti; Polcik, Laura; Dannewitz Prosseda, Svenja; Hartmann, Tanja Nicole (Frontiers in Cell and Developmental Biology, 2022)
The bone marrow microenvironment provides critical cues for hematopoietic stem cell (HSC) self-renewal and differentiation and contributes to their malignant conversion. The microenvironment comprises a complex mixture of multiple cell types, soluble factors, and extracellular matrix in specialized regions termed ‘niches.’ Positioning of the various cellular players within these niches depends on their repertoire of adhesion molecules and chemotactic signaling, involving integrins and chemokine receptors and the corresponding intracellular players such as kinases and GTPases. The mechanical role of adhesion is to control the strength and morphology of the cell-cell and cell-extracellular matrix contacts and thereby the energy needed for the optimal localization of cells to their surroundings. While it is clear that biomechanical adhesive bonds are energetically expensive, the crosstalk between cell adhesion and metabolic pathways in the normal and malignant microenvironment is far from understood. The metabolic profile of the various cell types within the niche includes key molecules such as AMPK, glucose, mTOR, and HIF-1α. Here, we describe our most recent understanding of how the interplay between adhesion and these metabolic components is indispensable for bone marrow niche stability. In parallel, we compare the altered crosstalk of different cell types within the bone marrow niches in hematological malignancies and propose potential therapeutic associations.